HIV/AIDS Prevention for Children as Victims of Sexual Abuse in Pari - Lidya Rahmadani Hasibuan (Yayasan Multidimensi Kreatif, 2025)
Sexual violence against children is a moral offense, and sexual harassment is two forms of moral violations that are not only national legal problems in a country but are also global legal problems for all countries. Child sexual abuse can be a means of spreading HIV/AIDS, especially if the perpetrator is HIV-positive. HIV/AIDS transmission to children can also occur from mother to child during pregnancy, childbirth, or breastfeeding. The recent surge in cases of sexual violence against children can be said to be multifactorial. These factors can be identified as two: internal and external. Internal factors are causes originating from within the perpetrator of sexual violence, such as psychological factors, biological factors, moral factors, revenge factors, and past trauma. Meanwhile, external factors can be identified as follows: cultural factors, economic factors, factors of minimal collective awareness of child protection in educational environments, factors of exposure to child pornography and adult pornography that victimizes children, factors of weak law enforcement and relatively light threats of punishment, factors of disharmony between legislative products related to children's issues, factors of children in disaster and emergency situations.